Pengaruh E-service Quality dan Online Customer Review Terhadap Customer Loyalty Generasi Z Berusia 18 - 28 Tahun: Studi Kasus pada Pengguna Marketplace Tokopedia Kota Bandung - Rahmat Ardi Yansa Jamlean; Aditya Yudanegara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study is motivated by the increasing use of digital services and the changing consumer behavior, particularly of Generation Z, in utilizing marketplace platforms such as Tokopedia. The integration of services between Tokopedia and TikTok Shop in 2024 has further altered users’ expectations regarding digital service quality and the credibility of online reviews in the decision-making process. This study aims to analyze the effect of E-Service Quality (X1) and Online Customer Review (X2) on Customer Loyalty (Y) among Tokopedia users aged 18 – 28 years. The research employs a descriptive - verificative method with a quantitative approach. A total of 385 respondents were selected using purposive sampling. Data analysis was conducted using SPSS version 31, including validity and reliability tests, descriptive analysis, verificative analysis, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results indicate that E-Service Quality (X1) has a significant effect on Customer Loyalty, with t count = 8.085 > t table = 1.966 and Sig < 0.001. Online Customer Review (X2) also significantly influences Customer Loyalty, with t count = 27.161 > t table = 1.966 and Sig < 0.001. The simultaneous test shows that both variables significantly affect Customer Loyalty, with F count = 1079.233 > F table = 3.02 and Sig < 0.001. Additionally, the R² value of 0.850 indicates that 85% of the variation in Customer Loyalty can be explained by E-Service Quality (X1) and Online Customer Review (X2). Overall, this study concludes that digital service quality and online customer reviews play a crucial role in shaping Tokopedia users’ loyalty, particularly among Generation Z, who heavily rely on digital experiences and social validation before making a purchase. These findings provide managerial implications, suggesting that improving digital service quality and managing credible customer reviews can be an effective strategy to maintain consumer loyalty.